Analysis of the influence of green brand image, green satisfaction and green trust on green brand equity - Erlyna Hidyantari Hidyantari; Rd. Nia Kania Kurniawati; Bambang Purwoko; Ahmad Gamal; Mira Gayatri Kartika (Enrichment : Journal of Management, 2022)
This study aims to determine and explain the effect of green brand image, green satisfaction and green trust on green brand equity. The type of research used is explanatory with a quantitative approach. The population in this study were students of the Faculty of Economics & Business Semester VII and were still active at W.R. University. Supratman Surabaya. The sample used in this study was 62 respondents who were taken using purposive sampling and data collection methods using questionnaires or online questionnaires. Data analysis used is descriptive statistical analysis and multiple linear regression analysis. The research data was processed using multiple linear regression with the SPSS version 23 program. The results of this study indicate that green brand image has no effect on green brand equity, while green satisfaction and green trust have an effect on green brand equity of Sostro tea box products.